3-(1-Adamantyl)-6-methyl-3-(3-methylbenzyl)isochroman-1-one - Eva Babjaková; Marek Nečas; Robert Vícha (Acta Crystallographica Section E, 2009)
In the title compound, C28H32O2, the oxanone ring adopts distorted half-boat conformation with the following Cremer and Pople puckering parameters: Q = 0.619 (2) Å, θ = 0.75 (19) and ϕ = 172 (13)°. The dihedral angle betwen two benzene rings is 21.32 (7)°. The adamantane unit consists of three fused cyclohexane rings in classical chair conformations, with absolute values of C—C—C—C torsion angles in the range 57.5 (2)–60.9 (2)°. Weak interactions of the type C—H...O link molecules of each enantiomer into chains parallel to the b axis and lying about inversion centers. The crystal packing is also stabilized by intermolecular π-π stacking interactions [centroid–centroid distance of 3.8566 (11) Å].